The Influence of Principal’s Leadership and Teachers’ Professionalism on Teachers’ Performance - Elen Sujana; Tri Widayatsih; Suherman Suherman (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to analyze the influence of principal’s leadership and teachers’ professionalism on the performance of State Elementary School teachers in Suak Tapeh District, Banyuasin Regency, examining both partial and simultaneous effects. Employing a quantitative ex post facto approach, data were collected via questionnaires and documentation from a sample of 115 teachers and analyzed using SPSS. The results confirm three findings: (1) principal’s leadership significantly influences teachers’ performance; (2) teachers’ professionalism significantly influences performance; and (3) both factors together exert a stronger, synergistic combined influence. The novelty of this research lies in its empirical demonstration of this synergy within a specific Indonesian district context, highlighting how leadership and professionalism interact to enhance outcomes. A key practical implication is the necessity for integrated school improvement policies that concurrently develop transformational leadership in principals and continuous professional growth for teachers. This study contributes to the field of educational management by providing evidence that teachers’ performance is optimally strengthened through dual-focused interventions targeting both administrative leadership and individual professional competence, offering a actionable model for district-level planning.